Economic study for the creation of a tilapia marketing center in the Taura parish of the naranjal canton (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2021)
The Naranjal canton belongs to the province of Guayas and has 67,976 inhabitants. It is made up of 96 precincts, 4 rural parishes that are Santa Rosa de Flandes, JesúsMaría, San Carlos and Taura; made up of 28,420 inhabitants, 41.81% of the total and the urban as the cantonal head of Naranjal made up of 39,555 inhabitants, 58.19% of the total according to the study by (INEC-CPV, 2010). For the development of this investigation, only one of the parishes of Naranjal, Taura was taken into account. The economic activity of the Naranjal canton is focused on agriculture and fish farming, for which reason the Guayas prefecture and the Naranjal municipality are providing financing for the development of these activities to sustain the economy of their parishes. From a practical point of view, the creation of the shopping center will help to standardize prices by generating fair trade. The vast majority of producers always abide by the prices proposed by their buyers and even the producers themselves enter into a price fight or also called cannibalism; where producers always offer less than their competition simply by selling their perishable products. On the part of the economic convenience of the marketing center “Mr. del Mar ”had to be evaluated through four different methods, among which are: the cost-benefit ratio, whose result was 1.38; which means that for each dollar unit invested, $ 1.38 will be obtained; recovery period, whose recovery year will be in the fourth with a value of $ 27,825.63 USD and from that period it would begin to generate profits; the net present value resulted in the value of $ 20,783.90 USD and an interest rate of return with 20.99%. Which concludes that the project “Mr. del Mar ”is feasible.
Keywords: economic study; marketing center; marketing strategies; investment project; financial budget